Safety, Tolerability, Pharmacokinetics, Pharmacodynamics, and Immunogenicity of ALXN1820 (Tarperprumig) in Healthy Adults: Results of a Phase I Study - Avner Sandhu; Tong Shen; Paz Martin Herrero; Chao‐Xing Yuan; Samirah Qureshi; Xiaoyu Jiang; Ye Sheng; Christoph Gasteyger; Yang Dai (Clinical and Translational Science)
ABSTRACT Properdin is an endogenous positive regulator of the complement alternative pathway (AP). Tarperprumig (ALXN1820), a novel humanized bispecific antibody, binds properdin and albumin and is being developed to treat complement‐mediated diseases. This phase I, randomized, double‐blind, placebo‐controlled trial assessed the safety, tolerability, pharmacokinetics (PK), pharmacodynamics, and immunogenicity of tarperprumig in healthy adult participants. In cohorts 1 to 4 and 6, single doses of tarperprumig were administered via subcutaneous (SC) injection (12.5, 50, 150, 450, and 1200 mg doses). In cohorts 8 and 9, the 150 mg dose was given via SC injection once weekly for 5 doses. In cohort 5, a single dose of 450 mg was administered via intravenous infusion. Sixty participants were randomized (3:1) to tarperprumig or placebo. There were no discontinuations due to adverse events (AEs) in participants receiving tarperprumig. There were no serious AEs, events of serious infection, or deaths. No N. meningitidis infections occurred. Most AEs were mild and not treatment related. Tarperprumig exposure resulted in linear dose proportionality among all but one cohort. Mean absolute bioavailability of tarperprumig was 94%. AP activity decreased rapidly after tarperprumig administration. Complete AP inhibition (< 1% of baseline value) was observed in all cohorts except for cohort 1 (12.5 mg SC). There was no change in complement classical or lectin pathway activity. Antidrug antibody titers were mostly low and did not impact PK. Tarperprumig was well tolerated and completely inhibited the AP in healthy adults. These results support continued investigation of tarperprumig to treat diseases involving complement activation. Trial Registration: EudraCT: 2021–002472‐39/NCT04631562